(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The primary objective of this study is to investigate the impacts of Brownian motion and thermophoresis dispersion on the behavior of magnetohydrodynamic (MHD) Casson nanofluid boundary layer flow over a non-linear inclined permeable stretching surface. This analysis takes into consideration convective constraints, thermal radiation, and chemical reactions. Nonlinear ordinary differential equations (ODEs) are derived from governing nonlinear partial differential equations (PDEs) using appropriate similarity transformations. The study quantifies various engineering parameters, such as skin friction, Nusselt number, and Sherwood number, while elucidating their influence on the velocity, temperature, and concentration profiles through graphical representations.